Anguilla-Overseas Territory of the United Kingdom : Assessment of the Supervision and Regulation of the Financial Sector-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report, 2003)
Anguilla is in the process of strengthening its legal and supervisory framework, which includes the creation of an operationally independent regulatory body, the Financial Services Commission. Priority should be given to improving the system for suspicious transaction reports, enhancing the customer due diligence requirements for introduced business, and conducting onsite inspections of company and trust service providers. The aim is to issue regulatory and industry codes that broadly meet the recommended best practices as contained in the draft Offshore Group of Banking Supervisors' Statement.